2005
DOI: 10.1189/jlb.0604341
|View full text |Cite
|
Sign up to set email alerts
|

BALB/c mice have more CD4+CD25+ T regulatory cells and show greater susceptibility to suppression of their CD4+CD25− responder T cells than C57BL/6 mice

Abstract: Increasing evidence indicates that CD4(+)CD25(+) T regulatory (Treg) cells control a wide spectrum of immune responses. The initial identification of CD4(+)CD25(+) Treg cell as a "professional suppressor" was based on observations made in BALB/c mice. This mouse strain is well known to preferentially develop T helper cell type 2 responses, to be more susceptible to intracellular parasite infection, to have a higher tumor incidence, and to be more resistant to the induction of autoimmune diseases, as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 51 publications
10
77
0
Order By: Relevance
“…Broadly similar findings have also been reported in TCR-insHEL mice (34,36) and therefore it is unlikely that these cells account for the difference in the severity of pancreatic and retinal disease. The relative absence of a significant role for this population in both models may be due to the high affinity of the 3A9 TCR and may also reflect strain differences as endogenous Treg number has been shown to be dependent on background (55,56). Our findings do not exclude an important role for Tregs in retinal tolerance and previous work has demonstrated that the severity of IRBP-induced EAU in WT mice is increased following depletion of CD4 ϩ CD25 ϩ cells (8).…”
Section: Discussionsupporting
confidence: 42%
“…Broadly similar findings have also been reported in TCR-insHEL mice (34,36) and therefore it is unlikely that these cells account for the difference in the severity of pancreatic and retinal disease. The relative absence of a significant role for this population in both models may be due to the high affinity of the 3A9 TCR and may also reflect strain differences as endogenous Treg number has been shown to be dependent on background (55,56). Our findings do not exclude an important role for Tregs in retinal tolerance and previous work has demonstrated that the severity of IRBP-induced EAU in WT mice is increased following depletion of CD4 ϩ CD25 ϩ cells (8).…”
Section: Discussionsupporting
confidence: 42%
“…It has been reported that Tregs overexpress a subset of Th2 response genes including interleukin (IL)-10 and transforming growth factor beta (TGF-␤), 17 suppressing Th1 responses and resulting in Th2 polarization. 18,19 BALB/cJ mice that are known to exhibit a Th2-phenotype 20 have increased numbers of Tregs compared with A/J mice that predominantly mount Th1 immune responses. 21 Others have shown that BALB/cJ mice display nonprotective Th2 responses and these mice are susceptible to infection with other pathogens, including the intracellular parasite Leishmania major, whereas mice that develop a Th1 immune response are protected from infection.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, TNF-␣ polymorphisms that lead to elevated TNF-␣ levels have been related to decreased T reg cell numbers (28), and anti-TNF-␣ therapy was shown to increase T reg cell levels in asthma and Crohn's disease (27,39). Contrary to this hypothesis, numbers of T reg cells were decreased in the thymus and lymphoid tissue of C57BL/6 mice compared with BALB/c mice (10). However, the potential differences in the number and function of T reg cells in the lungs of various mouse strains have yet to be clarified.…”
Section: Discussionmentioning
confidence: 41%